2021
DOI: 10.2500/aap.2021.42.210058
|View full text |Cite
|
Sign up to set email alerts
|

Impact of type 2 targeting biologics on acute exacerbations of chronic rhinosinusitis

Abstract: Background: Acute exacerbations of chronic rhinosinusitis (AECRS) are associated with significant morbidity and decreased quality of life. There are sparse data assessing the real-world impact of biologics on AECRS. Objectives: We sought to determine the impact of type 2‐targeting biologics on the frequency of medication use for AECRS episodes. Methods: Antibiotic and/or systemic corticosteroid courses for AECRS were identified in a retrospective study from November 2015 to February 2020, at a single academ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Some studies have defined an AECRS as any acute worsening of sinonasal symptomatology reported by the patient, 16 whereas others have followed this definition but used quantitative validated patient‐reported outcomes to verify worsening symptomatology 17 . Other studies have used surrogate measures of AECRS to quantify AECRS frequency, such as the frequency of sinus infections and/or frequency of rescue medication (i.e., antibiotics or oral corticosteroids) 2,15,18–21 . Finally, endoscopic findings have also been used to define AECRS in the literature.…”
Section: Definitionmentioning
confidence: 99%
See 4 more Smart Citations
“…Some studies have defined an AECRS as any acute worsening of sinonasal symptomatology reported by the patient, 16 whereas others have followed this definition but used quantitative validated patient‐reported outcomes to verify worsening symptomatology 17 . Other studies have used surrogate measures of AECRS to quantify AECRS frequency, such as the frequency of sinus infections and/or frequency of rescue medication (i.e., antibiotics or oral corticosteroids) 2,15,18–21 . Finally, endoscopic findings have also been used to define AECRS in the literature.…”
Section: Definitionmentioning
confidence: 99%
“…Type 2 cytokines produced during AECRS can mechanically weaken the epithelial barrier and increase permeability, thus leading to a susceptibility for microbial invasion and infection 20,28 . Furthermore, baseline epithelial inflammation in CRS can be exacerbated by viral infections and the subsequent host response, further diminishing epithelial function 29 .…”
Section: Pathophysiologymentioning
confidence: 99%
See 3 more Smart Citations